The use of AI tools in english language teaching: educational challenges and pedagogical solutions - Koliada, I. V.; Sukhanova, Tetiana Yevhenivna (Університет Григорія Сковороди в Переяславі, 2026)
The article provides a comprehensive analysis of the use of artificial intelligence tools in teaching English at higher education institutions. The study examines current areas of AI application in language education, including automated generation of learning materials, assessment of written assignments, development of lexical and grammatical skills, and personalization of learning. Particular attention is paid to the drawbacks and risks of AI integration, such as reduced student autonomy, the emergence offormulaic language, violations of academic integrity, and methodological inaccuracies in AI generated content. The issue of excessive student reliance on AI platforms for completing assignments and projects is analyzed as a factor that negatively affects communicative competence development. The paper proposes pedagogically grounded strategies for controlling and preventing the overuse of AI tools, as well as outlines conditions for their effective and ethical implementation as supportive learning resources. The findings may be useful for university teachers, curriculum designers, and educational researchers.

У статті здійснено комплексний аналіз використання інструментів штучного інтелекту у процесі викладання англійської мови в закладах вищої освіти. Розглянуто сучасні напрями застосування ШІ в мовній підготовці студентів, зокрема автоматизоване створення навчальних матеріалів, перевірку письмових робіт, розвиток лексико граматичних навичок та індивідуалізацію навчання. Основну увагу приділено недолікам і ризикам інтеграції ШІ, серед яких зниження рівня самостійного мислення студентів, формування шаблонного мовлення, порушення принципів академічної доброчесності та методичні помилки під час створення контенту викладачами. Проаналізовано проблему надмірного використання ШІ платформ студентами під час виконання письмових робіт, домашніх завдань і проєктів, що негативно впливає на формування комунікативної компетентності. Запропоновано педагогічно обґрунтовані шляхи контролю та запобігання зловживанню інструментами ШІ, а також визначено умови їх доцільного використання як допоміжного засобу навчання. Матеріали статті можуть бути використані викладачами іноземних мов, методистами та розробниками освітніх програм.
Keywords: artificial intelligence; English language teaching; higher education; academic integrity; educational technologies; штучний інтелект; викладання англійської мови; вища освіта; академічна доброчесність; освітні технології